Study of Sex Differences in Duloxetine Efficacy for Depression in Transgenic Mouse Models - Xu, Yong; Ma, Lei; Jiang, Wei; Li, Yuhong; Wang, Gang; Li, Rena (Frontiers in Cellular Neuroscience, 2017)
Clinical evidences show sex differences in risk of developing depressive disorders as well as effect of antidepressants in depression treatment. However, whether such a sex-dependent risk of depression and efficacy of antidepressants is dependent on endogenous estrogen level remain elusive. The aim of this study is to explore the molecular mechanisms of sex differences in antidepressant duloxetine. In the present study, we used genetic knockout or overexpression estrogen-synthesizing enzyme aromatase (Ar) gene as models for endogenous estrogen deficiency and elevation endogenous estrogen, respectively, to examine the anti-depressive efficacy of duloxetine in males and females by force swimming test (FST). We also measured the sex-specific effect of duloxetine on dopamine and serotonin metabolisms in frontal cortex and hippocampus. Elevation of brain endogenous estrogen in male and female mice showed a reduction of immobility time in FST compared to control mice. Estrogen deficiency in females showed poor response to duloxetine treatment compared to sex-matched wildtype or aromatase transgenic mice. In contrast, male mice with estrogen deficiency showed same anti-depressive response to duloxetine treatments as aromatase transgenic mice. Our data showed that the sex different effect of endogenous estrogen on duloxetine-induced anti-depressive behavioral change is associated with brain region-specific changes of DA and 5-HT system. Endogenous estrogen exerts antidepressant effects in both males and females. Lacking of endogenous estrogen reduced antidepressive effect of duloxetine in females only. The endogenous estrogen level alters 5-HT system in female mainly, while both DA and 5-HT metabolisms were regulated by endogenous estrogen levels after duloxetine administration.